(untitled) (e-Journal of Linguistics, 2023)
This study aim of the research is to identify the type of deixis and the dominant type of deixis in the lyrics of Madison Beer’s song Reckless. This study is a type of qualitative research. Data collection techniques include listening to songs and analyzing Madison Beer’s song "Reckless." The findings of this study include all types of deixis found in the person (64 data), spatial (11 data), temporal (8 data), and social (5 data) deixis found in the lyrics of Madison Beer’s song Reckless. People’s deixis is most frequently found in Reckless lyrics. The majority of the deixis found in this study are people’s deixis, such as I and You. While the plural deixis of people found is We which is addressed to the listener.